Features of the Formation of a Competitive Environment in the Areas of Natural Monopoly in Uzbekistan - Samieva Maftuna (Antis Publisher, 2024)
This scientific article covers the features of the formation of a competitive environment in the fields of natural monopolies in Uzbekistan. Natural monopolies cause the emergence of an unhealthy environment of comfort, which can be caused in the market, the circumstances of the origin of unfavorable situations in the economy are studied. By regulating natural monopolies, an important role and peculiarities of the state are shown in the formation of a competitive environment.